Changes in back squat bar velocity and perceived muscle soreness following a standardised rugby league match simulation - Callaghan, D.; Elsworthy, N.; Guy, J.; Kean, C. O. (ISBS Proceedings Archive (Michigan), 2023)
This study examined changes in back squat bar velocity and perceived muscle soreness following a rugby league match simulation protocol. Twenty male rugby league players (age: 19.8 ± 0.7 yrs) were recruited for this study. Back squat bar velocity and perceived muscle soreness of the lower body were collected on four days surrounding a match simulation: -24 h (prior to match simulation), +0 h (after the match simulation), +24 h and +48 h. Compared to baseline (-24h), there were non-significant decreases in maximum (dz=-0.50, moderate) back squat bar velocity +0 h. There was a significant increase in perceived muscle soreness at +0h only (p=0.003). Results suggest that elevated muscle soreness may not indicate impaired neuromuscular performance and highlight the importance of monitoring fatigue via multiple measures to ensure appropriate coaching decisions are made.